2022
DOI: 10.3390/ijms23179875
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Coronary Artery Disease and Diabetes Revealed by scRNA-Seq and CITE-Seq of Human CD4+ T Cells

Abstract: Despite the decades-old knowledge that males and people with diabetes mellitus (DM) are at increased risk for coronary artery disease (CAD), the reasons for this association are only partially understood. Among the immune cells involved, recent evidence supports a critical role of T cells as drivers and modifiers of CAD. CD4+ T cells are commonly found in atherosclerotic plaques. We aimed to understand the relationship of CAD with sex and DM by single-cell RNA (scRNA-Seq) and antibody sequencing (CITE-Seq) of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…To study the relationship between CAD and NK cells in humans, we analyzed PBMC CITE-seq data from a cohort of 61 patients diagnosed with a low or high CAD severity score (percent stenosis of each artery segment; CAD low : 0-6, or CAD high : x > 30, and as was previously defined: GSE190570) 22 . Thirty-one patients were diagnosed with T2DM (type 2 diabetes).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the relationship between CAD and NK cells in humans, we analyzed PBMC CITE-seq data from a cohort of 61 patients diagnosed with a low or high CAD severity score (percent stenosis of each artery segment; CAD low : 0-6, or CAD high : x > 30, and as was previously defined: GSE190570) 22 . Thirty-one patients were diagnosed with T2DM (type 2 diabetes).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the tubes containing the PBMCs were centrifuged at 400 × g for 5 minutes. The cells were then resuspended in a combination of 51 AbSeq antibodies, with each antibody added at a volume of 2 μL and 20 μL of BD’s Stain Buffer solution 22 . This resuspension process was per-formed on ice for 30-60 minutes according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary angiography allows us to apply a well-validated quantitative atherosclerosis severity score, known as the Gensini score, that has proven to be highly effective in predicting the risk of future cardiovascular events. Subjects within our study were stratified based on Gensini scores as either having low CAD (Gensini scores ≤ 6) or high CAD (Gensini scores > 32) [ 12 , 13 ]. We included both males and females in our study, and all statistical analyses were adjusted for statin use, smoking, and diabetes as covariates.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of ours and others, using high dimensional immunoprofiling methods, have identified multiple immune cells present in the mouse atherosclerotic aorta, including previously unknown immune cell subclusters [ 10 , 11 ]. In human clinical atherosclerosis, we and others have reported changes in human peripheral blood T and B cells [ 12 , 13 ] and plaque-localized immune cells and macrophages [ 14 , 15 , 16 ]. We have reported detailed phenotypic heterogeneity in human peripheral blood monocytes from healthy individuals [ 17 ].…”
Section: Introductionmentioning
confidence: 99%